Peranan Program Dakwah Yayasan Al-Muslim terhadap Pemahaman Keagamaan Masyarakat Komplek Cibeunying Permai Kecamatan Cibeunying Kaler Kota Bandung - Muhamad Nurul Basyir; Muhammad Wildan Yahya (UNISBA Press, 2022)
Abstract. This research is about da'wah which has been done by many previous researchers. However, there is no research that examines the influence of a foundation's da'wah program with the object of religious understanding. On that basis, this study focuses on,